Landscape Composition and Fungicide Exposure Influence Host–Pathogen Dynamics in a Solitary Bee. Issue 1 (28th November 2020) - Krichilsky, Erin; Centrella, Mary; Eitzer, Brian; Danforth, Bryan; Poveda, Katja; Grab, Heather
Abstract: Both ecosystem function and agricultural productivity depend on services provided by bees; these services are at risk from bee declines which have been linked to land use change, pesticide exposure, and pathogens. Although these stressors often co-occur in agroecosystems, a majority of pollinator health studies have focused on these factors in isolation, therefore limiting our ability to make informed policy and management decisions. Here, we investigate the combined impact of altered landscape composition and fungicide exposure on the prevalence of chalkbrood disease, caused by fungi in the genus Ascosphaera Olive and Spiltoir 1955 (Ascosphaeraceae: Onygenales), in the introduced solitary bee, Osmia cornifrons (Radoszkowski 1887) (Megachilidae: Hymenoptera). We used both field studies and laboratory assays to evaluate the potential for interactions between altered landscape composition, fungicide exposure, and Ascosphaera on O. cornifrons mortality. Chalkbrood incidence in larval O. cornifrons decreased with high open natural habitat cover, whereas Ascosphaera prevalence in adults decreased with high urban habitat cover. Conversely, high fungicide concentration and high forest cover increased chalkbrood incidence in larval O. cornifrons and decreased Ascosphaera incidence in adults. Our laboratory assay revealed an additive effect of fungicides and fungal pathogen exposure on the mortality of a common solitary bee. Additionally, we utilized phylogenetic methods and identified four species of Ascosphaera with O. cornifrons, both confirming previous reports and shedding light on new associates. Our findings highlight the impact of fungicides on bee health and underscore the importance of studying interactions among factors associated with bee decline.